Comparative Assessment Of Raw And Downscaled CMIP6 Multi-Model Ensembles For Projecting Temperature And Precipitation Dynamics In The Tamor River Basin - Shrestha, Narayan; Bhattarai, Devi Prasad (Journal of Advanced College of Engineering and Management, 2026)
This study presents a comparative assessment of raw and downscaled CMIP6 multi-model ensembles for projecting temperature and precipitation dynamics in the Tamor River Basin. Utilizing a six-model ensemble under SSP245 and SSP585, the research quantifies the added value of high-resolution NEX-GDDP data and secondary local bias correction. Results indicate a consistent warming trend, with minimum temperatures rising faster than maximums, narrowing the diurnal range. Under SSP585, the downscaled ensemble projects a +4.22°C temperature increase, surpassing +3.72°C projected by raw GCMs. Similarly, downscaling amplifies the wetting signal, projecting a 54% increase in annual precipitation compared to 46% in raw outputs, with significant intensification during monsoon (JJAS) and post-monsoon (ON). These findings suggest that raw GCMs may underestimate thermal stress and hydrological intensification in complex Himalayan terrains. Overall, downscaled projections provide improved spatial representation and more consistent climate signals, offering a reliable basis for hydroclimatic assessment.